Parents' Leadership in The Development of Children's Education: Children Education - Firman Mansir (Jayapangus Press, 2022)
This research explains the importance of children's education in the context of social, religious, and state life from the perspective of Islamic education. The purpose of this study is to explain and find out parents’ leadership in children’s education. The study of Islamic education is very focused on the dynamics of life for children in the family and the surrounding environment. The importance of education for children can form a good personality or character according to the study of Islamic education. This research show that parents’ leadership needs to be aligned with the concept of children's education in the perspective of Islamic education is based on the values of the Qur'an and al-Hadith as fundamental things in the educational life of children to become superior, devoted, and tough (pious) children. Children's education starts from the knowledge of monotheism, morals, and worship and teaches children to understand and practice the Qur'an. This study utilizes a qualitative approach so that data processing is conducted through literature analysis specially literature description. Therefore, in Islamic education, the developmental concern for children contains the values to be achieved to realize the goals of Islamic education, and in the end, it can become a strength to deal with relationships in a very plural society.